Chlamydia Treatment Practices and Time to Treatment in Massachusetts: Directly Observed Therapy Versus Pharmacy Prescriptions. (September 2021) - Platt, Laura; Elder, Heather; Bassett, Ingrid V.; Molotnikov, Lauren; Klevens, Monina; O'Connor, Erin; Leach, Dylan; Roosevelt, Kathleen; Hsu, Katherine
Background: Directly observed therapy (DOT) is recommended for the treatment of chlamydia, however pharmacy prescriptions are frequently used. Adherence to DOT and the association between treatment method and time to treatment is unknown. Methods: We conducted a retrospective review of a randomized 2% of laboratory-confirmed chlamydia infections reported to the Massachusetts Department of Public Health from January 1, 2019 to May 31, 2019. Clinicians and pharmacies were contacted to ascertain treatment methods and timing. We assessed frequency of DOT and pharmacy prescriptions in the treatment of chlamydia infection in Massachusetts. We used log rank test to compare time to treatment initiation for patients receiving DOT versus pharmacy prescriptions. Data were stratified according to whether treatment was empiric or laboratory-driven. Key results: We ascertained full outcomes for 199 patients. Eighty patients received DOT and 119 patients received pharmacy prescriptions. DOT was more common among those receiving empiric treatment and pharmacy prescriptions were more common among those receiving laboratory-driven treatment. The median time to treatment was 1.5 days for patients treated with DOT and 3 days for those treated with pharmacy prescriptions. For both groups, the median time to treatment for empiric therapy was 0 days and for laboratory-driven therapy was 4 days. The differences in time to treatment were not statistically significant. Conclusions: Pharmacy prescriptions are frequently used for the treatment of chlamydia in Massachusetts. We did not observe a significant difference in the time to treatment between DOT and pharmacy prescriptions.